2009
DOI: 10.1007/s11368-009-0122-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vegetation restoration and slope positions on soil aggregation and soil carbon accumulation on heavily eroded tropical land of Southern China

Abstract: Background aim and scope Soil organic carbon (SOC) accumulation is strongly affected by soil erosion and deposition that differ at slope positions of a watershed. However, studies on the effects of topography on soil aggregation and SOC dynamics, especially after the implementation of vegetation restoration, are rare. Poorly understood mechanisms and a lack of quantification for the suite of ecological benefits brought by the impacts of topography after planting further obstructed our understanding of terrestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 34 publications
(37 reference statements)
3
46
0
2
Order By: Relevance
“…The erosion of fluvial slopes, strongly resulting from anthropic actions, has directly interfered in the survival of species of fauna and flora; the biological communities in aquatic environments; reduction of agricultural areas; as well as to intensify the silting of watercourses, making it difficult to navigate, fish and public water supply (TANG et al, 2010;RIBEIRO et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The erosion of fluvial slopes, strongly resulting from anthropic actions, has directly interfered in the survival of species of fauna and flora; the biological communities in aquatic environments; reduction of agricultural areas; as well as to intensify the silting of watercourses, making it difficult to navigate, fish and public water supply (TANG et al, 2010;RIBEIRO et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In China, forest plantation area increased to 69.33 million ha in 2014, becoming the largest around the world according to the data of the eighth national forest resources inventory (www.xinhuanet.com/zhibo/20140225a/zhibo.htm). Although these numbers are impressive, the quality of forest establishment, rather than just the acreage, is critical to meet growing environmental, social, and economic demands on a finite land base (Tang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A decrease of aggregates stability is evident in the exposed parts of the slope, mainly due to the intensive soil organic carbon removal and subsoil exposing. Tang et al (2010) demonstrated a significant difference of the WSA index between the shoulder and toe slope positions, the WSA at the toe slope being significantly higher than that at the shoulder slope. The result was explained by the fact that the small-sized water stable aggregates displaced at the shoulder slope, transported by surface flow, and redeposited at the toe slope accelerated the development of WSA at the toe slope location.…”
Section: Resultsmentioning
confidence: 82%
“…Most of the studies emphasise the relation between organic carbon, soil erosion, and, the role of the soil aggregation in organic carbon protection in depression areas (Six et al 2004;Berhe et al 2007;Yadav & Malanson 2007). Nevertheless, the studies on the soil aggregate stability spatial distribution and its relationship with topography are rather rare and focused more on the assessment of soil aggregate stability in different parts of the slope system (Rhoton et al 2006;Tang et al 2010) than on their direct relationship with topographic derivatives (Cantón et al 2009). …”
mentioning
confidence: 99%